CLINICAL AND PATHOLOGICAL EFFECTS OF PARENTERALLY ADMINISTERED CHLOROFORM AND AQUEOUS EXTRACT OF CALOTROPIS PROCERA IN RABBITS - M. Ahmad; M. Ashraf; M. S. Khan; A. Javeed; A. Z. Durrani; I. Altaf; M. U. R. Khan¶; I. Ahmed¶; M. Avais (Journal of Animal and Plant Sciences, 2014)
Study was carried out to evaluate the pathological effects of parenterally administrated “Calotropis procera extracts” in rabbits. Fresh flowery buds of C. procera were collected from the District Lahore, Pakistan. Total of 35 rabbits of either sex were purchased from the animal house of University of Veterinary and Animal Sciences, Lahore. Rabbits were randomly distributed in to 3 major groups (A= C. procera chloroform extract, B= C. procera water extract, C= Normal saline). Groups A and B were further subdivided into three sub-groups (A1, A2, A3, B1, B2 and B3) of 5 and C (n=5) were used as a control group. Biochemical findings showed a significant increase (P<0.05) in serum level of creatinine, urea and ALT in group A3 at day 30 as compared with group C. Gross lesions consisting of severe hemorrhages, lung emphysema in group A3 and lobular congestion, multifocal emphysema were observed in group B3. Histopathological lesions such as hyperplasia of Kupffer cells, hepatic cell degeneration and eruption of bronchiole epithelium were observed in group A3. It is concluded that higher dose (10 mg/kg BW) of chloroform extract of the C. procera had cardiotoxic and hepato-renal toxic effect and cause lungs emphysema in rabbits.
Keywords: Calotropis procera; ALT; Urea; Creatinine; Rabbits